“Trust people you’ve never worked with” – A social network visualization of teamwork, cohesion, social support, and mental health in NHS Covid personnel - Schilling, Stefan; Armaou, Maria; Morrison, Zoe; Carding, Paul; Bricknell, Martin; Connelly, Vincent (Frontiers in Psychology, 2024)
Background: The unprecedented rapid re-deployment of healthcare workers from different care pathways into newly created and fluid COVID-19 teams provides a unique opportunity to examine the interaction of many of the established non-technical factors for successful delivery of clinical care and teamwork in healthcare settings. This research paper therefore aims to address these gaps by qualitatively exploring the impact of COVID work throughout the pandemic on permanent and deployed personnel's experiences, their ability to effectively work together, and the effect of social dynamics (e.g., cohesion, social support) on teamwork and mental health. Methods: Seventy-five interviews were conducted across the UK between March and December 2021 during wave 2 and 3 of COVID-19 with 75 healthcare workers who were either permanent staff on Intensive Care/High Dependency Units used as COVID wards, had been rapidly deployed to such a ward, or had managed such wards. Work Life Balance was measured using the WLB Scale. Interview transcripts were qualitatively coded and thematic codes were compared using network graph modelling.Results: Using thematic network analysis, four overarching thematic clusters were found, (1) Teamwork, (2) Organizational Support & Management, (3) Cohesion & Social Support, and (4) Psychological Strain. The study has three main findings. First, the importance of social factors for teamwork and mental health, whereby team identity may influence perceptions of preparedness, collaboration and communication, and impact on the collective appraisal of stressful events and work stressors. Secondly, it demonstrates the positive and negative impact of professional roles and skills on the development of teamwork and team identity. The study identifies the more pronounced negative impact of COVID work on deployed personnel's workload, mental health, and career intentions, exacerbated by reduced levels of social support during, and after, their deployment. Conclusions: The analysis was able to highlight the interactive and interdependent role of social dynamics on teamwork, suggesting that besides technical skills and preparedness, group membership and perception of professional category may play a bigger role for teamwork than previously stated. It also highlights the potentially protective impact of team-membership on participants experience of their pandemic work, especially considering the length of the recent pandemic.